NITROGEN-POTASSIUM FERTILIZERS BASED ON AMMONIUM NITRATE FUEL WITH ASH ADDITION - Rasuljon Erkinov; Dilshoda Rozikova; Zulfikaxar Dexkanov (Galaxy International Interdisciplinary Research Journal, 2022)
The article defines the chemical composition of nitrogen-potassium fertilizers obtained by introducing ash into the melt of ammonium nitrate at mass ratios of ammonium nitrate: ash = 100 : (3-25) and a temperature of 180°C. The density and viscosity of the ammonium nitrate melt with the addition of ash in the temperature range 160-185°C were also determined, and the strength of the granules was determined at the above ratios of ammonium nitrate : ash.